Jaw osteonecrosis in patients treated with denosumab 120 mg with regular dental monitoring: 4-year retrospective study - Beaudouin Sophie; Scailteux Lucie-Marie; Lefeuvre Claudia; Gamby Romain; Cairon-Lejeune Sophie (EDP Sciences, 2021)
Background: Medication-related osteonecrosis of the jaw (MRONJ) is an expected, but rare adverse effect of denosumab. There are few data denosumab 120 mg related MRONJ occurrence when regular dental monitoring is planned. International and French recommendations do not detail the schedule of the follow-up visits, allowing local interpretations. Methods: The aim of this retrospective study was to describe our local experience of regular dental monitoring in patients receiving denosumab 120 mg. We included all ≥18-year-old patients exposed to denosumab 120 mg, bisphosphonate- and denosumab-naive, and with regular dental monitoring (pre-treatment and every 4 months after denosumab initiation) at the University Hospital Center, France, from 2015 to 2019. The crude incidence of denosumab-related osteonecrosis of the jaw was estimated per 100 person-years (95% confidence interval). Results: During the study period, 251 patients were included, of whom 77 did not attend the 1st follow-up visit at 4 months. Almost all patients had osteonecrosis of the jaw risk factors. Ten MRONJ cases were reported (four stage 0 and six stage 1). The crude incidence rate was 5.1 per 100 person-years (95% CI: 1.9-8.2). Denosumab was stopped in all patients who developed MRONJ, with favorable outcome for 3 cases and stabilization in 4 cases after osteonecrosis of the jaw management. Conclusion: This study suggested that a regular dental follow-up every 4 months may be a suitable option for prevention and early detection/treatment of MRONJ. A randomized study should be performed to determine the best dental monitoring schedule.